‘‘Time after time’’: A Quali-T method for assessing music's impact on well-being - DeNora, Tia (Co-Action Publishing, 2013)
This article considers the question of how to produce ecologically valid assessments of music's role as a health technology. To address this question, I consider critically some of the standard quantitative instruments used to assess well-being and quality of life. I suggest that these instruments do not lend themselves well to the production of ecologically valid assessments and understandings for two reasons: (1) the process of data elicitation is removed from everyday meanings and practices and therefore risks producing data that is an artifact of the situation in which it is elicited (2) standard, quantitative instruments are not neutral but are rather discursive texts that are inevitably imbued with a politics of expertise and an image of the health care client. For these reasons, I suggest that we consider the question of how to develop ecologically valid, client-centered assessment measures. To that end, I introduce a third critique of the standard quantitative instruments, namely that they are associated with, and promote, an ontology of wellness/illness that downplays the temporally variable and situationally emergent nature of both wellness/illness and musical interventions themselves. As an alternative mode of assessment, I suggest that we reconsider the value of singular case studies and I describe a set of principles that can assist researchers to produce ecologically valid assessments. To this end I introduce the concept of the musical event as a more ecologically valid means for illuminating the specific mechanisms by which music aids well-being. I suggest that the case study approach is temporally sensitive, that it lends itself to an emergent ontology of wellness/illness, and that it is client-centered (and can also be user-led).